Improving the admission process in a higher education institute using Lean Six Sigma: A case study - Shamsuzzaman, Mohammad; Khadem, Mohammad; Haridy, Salah; Shamsuzzoha, Ahm; Abdalla, Mohammad; Al-Hanini, Marwan; Almheiri, Hamdan; Masadeh, Omar (Emerald, 2023)
Purpose The purpose of this study is to implement lean six sigma (LSS) methodology to improve the admission process in a higher education institute (HEI). Design/methodology/approach In this study, case study research methodology is adopted and implemented through an LSS define-measure-analyze-improve-control (DMAIC) framework. Findings The preliminary investigation showed that the completion of the whole admission process of a new student takes an average of 88 min, which is equivalent to a sigma level of about 0.71 based on the targeted admission cycle time of 60 min. The implementation of the proposed LSS approach increased the sigma level from 0.71 to 2.57, which indicates a reduction in the mean admission cycle time by around 55%. This substantial improvement is expected not only to provide an efficient admission process but also to enhance the satisfaction of students and employees and increase the reputation of the HEI to a significant level. Research limitations/implications In this study, the sample size used in the analysis is considered small. In addition, the effectiveness of the proposed approach is investigated using a discrete event simulation with a single-case study, which may limit generalization of the results. However, this study can provide useful guidance for further research for the generalization of the results to wider scopes in terms of different sectors of HEIs and geographical locations. Practical implications This study uses several statistical process control tools and techniques through a LSS DMAIC framework to identify and element the root causes of the long admission cycle time at a HEI. The approach followed, and the lessons learned, as documented in the study, can be of a great benefit in improving different sectors of HEIs. Originality/value This study is one of the few attempts to implement LSS in HEIs to improve the administrative process so that better-quality services can be provided to customers, such as students and guardians. The project is implemented by a group of undergraduate students as a part of their senior design project, which paves the way for involving students in future LSS projects in HEIs. This study is expected to help to improve understanding of how LSS methodology can be implemented in solving quality-related problems in HEIs and to offer valuable insights for both academics and practitioners.
Keywords: Administrative process; Admission process; Higher educational institute; Lean six sigma; Service excellence; fi=Tuotantotalous|en=Industrial Management|